Long-term quality of integrated community case management care for children in Bugoye Subcounty, Uganda: a retrospective observational study - Miller, James S.; Mulogo, Edgar Mugema; Wesuta, Andrew Christopher; Mumbere, Nobert; Mbaju, Jackson; Bwambale, Shem; Stone, Geren S. (BMJ open, 2022)
Integrated community case management (iCCM) of childhood illness in Uganda involves protocol-based care of malaria, pneumonia and diarrhoea for children under 5 years old. This study assessed volunteer village health workers’ (VHW) ability to provide correct iCCM care according to the national protocol and change in their performance over time since initial training. VHWs affiliated with the Ugandan national programme provide community-based care in eight villages in Bugoye Subcounty, a rural area in Kasese District. The first cohort of VHWs began providing iCCM care in March 2013, the second cohort in July 2016. All children receiving iCCM care in 18 430 clinical encounters occurring between April 2014 and December 2018. The descriptive primary outcome measure was the proportion of patients receiving overall correct care, defined as adherence to the iCCM protocol for the presenting condition (hereafter quality of care). The analytic primary outcome was change in the odds of receiving correct care over time, assessed using logistic regression models with generalised estimating equations. Secondary outcome measures included a set of binary measures of adherence to specific elements of the iCCM protocol. Preplanned and final measures were the same. Overall, VHWs provided correct care in 74% of clinical encounters. For the first cohort of VHWs, regression modelling demonstrated a modest increase in quality of care until approximately 3 years after their initial iCCM training (OR 1.022 per month elapsed, 95% CI 1.005 to 1.038), followed by a modest decrease thereafter (OR 0.978 per month, 95% CI 0.970 to 0.986). For the second cohort, quality of care was essentially constant over time (OR 1.007 per month, 95% CI 0.989 to 1.025). Quality of care was relatively constant over time, though the trend towards decreasing quality of care after 3 years of providing iCCM care requires further monitoring.
Keywords: Children; Management care; Integrated community case